The Effects of Workload and Workplace Conflict on Employees’ Turnover Intention - Lestari Lestari; Atty Erdiana (Lensa Ilmiah: Jurnal Manajemen dan Sumberdaya, 2026)
Employee turnover intention has become a critical issue in human resource management because it often serves as an early indicator of actual employee turnover, which can negatively affect organizational performance and operational stability. This study aims to examine the effects of workload and workplace conflict on employee turnover intention at PT Pulau Nusantara Indonesia. A quantitative approach with an associative research design was employed. The population consisted of all 35 employees working at the company’s head office, and a saturated sampling technique was used, resulting in 35 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS. Prior to hypothesis testing, the data were subjected to validity, reliability, normality, multicollinearity, and heteroscedasticity tests. The results indicate that workload has a positive and significant effect on turnover intention (β = 0.402; p < 0.05), while workplace conflict also has a positive and significant effect and emerges as the most dominant predictor (β = 0.596; p < 0.05). Simultaneously, workload and workplace conflict significantly influence turnover intention (F = 251.252; p < 0.05), explaining 94.0% of the variance in turnover intention (R² = 0.940). These findings suggest that both task-related pressures and interpersonal conflicts contribute substantially to employees’ intentions to leave the organization. Therefore, organizations should implement integrated strategies that focus on workload management, conflict resolution, and the development of a supportive work environment to reduce turnover intention and improve employee retention.